The Politics of EU Gender Equality Policies: Prospects for Changing Gender Equality Paradigm at the EU - Nazlı Kazanoğlu (Ankara Avrupa Çalışmaları Dergisi)
Gender equality has long been a central theme of the European social model since the Maastricht Treaty. Using the example of work - life balance policies, this article aims to identify two successive periods and explore the changing policy paradigm with respect to gender equality at the EU. In so doing, the article draws on two conceptual approaches in terms of theoretical basis: (a) Esping-Andersen’s three welfare pillar conceptualisation and (b) genderised and de-genderised distinction. Drawing on a comprehensive literature review and the content analysis of official EU policy texts, the article contends that the EU gender policies have shifted away from serving to change the redistribution of work between men and women, towards improving women’s employment opportunities.